Revisiting two thousand hinge fractures in open wedge high tibial osteotomy with a fifty years review: the oscillating saw cannot replace the traditional “ear-hand” dialogue between osteotome and hammer to estimate the elastic modulus of bone - Bastard Claire; Haiat Guillaume; Hernigou Philippe (SICOT-J)
Background: Hinge fracture on the lateral part of the tibia (LHF) is a common complication of medial Open Wedge High Tibial Osteotomy (OWHTO). Many factors have been described as risks for these fractures, but no study has compared an osteotome or an oscillating saw to prevent LHF following OWHTO. Methods: This “propensity-score-matched” (PSM) study was conducted from data obtained in the literature from 1974 to November 2024. A total of 10,368 knees with OWHTO were identified. After 1:1 matching based on correction amount, posterior slope change, surgeon’s experience, the osteotome and oscillating groups comprised 2760 knees each. Results: Among the 5520 knees of the PSM population, the prevalence of LHF was 6.1% in the osteotome alone group (168 cases), and 22% in the oscillating saw group (607 cases). The osteotome group had a significant lower prevalence of hinge fracture than the oscillating saw group (OR, 0.23; 95% CI, 0.19 to 0.27; p < 0.0001) and a lower rate of clinically relevant hinge fractures with revision (OR, 0.34; 95% CI, 0.25 to 0.45; p < 0.001. Discussion: The osteotome may be an appropriate method for preventing hinge fractures following OWHTO.